Elite Upland Cotton Germplasm‐Pool Assessment of Fusarium Wilt Resistance in California. (1st November 2013) - Hutmacher, Robert B.; Ulloa, Mauricio; Wright, Steven D.; Campbell, B. Todd; Percy, Richard; Wallace, Ted; Myers, Gerald; Bourland, Fred; Weaver, David; Chee, Peng; Thaxton, Peggy; Zhang, Jinfa; et al.
Abstract : During the past 9 yr, a new race of Fusarium ( Fusarium oxysporum f. sp. vasinfectum [FOV Race 4]) has increasingly impacted cotton ( Gossypium spp.) in the San Joaquin Valley of California. To assess the vulnerability of upland cotton ( G. hirsutum L.) in California to FOV disease, elite upland germplasm lines from 13 U.S. public breeding programs across the Cotton Belt and commercial cultivars were evaluated for disease resistance to FOV Races 1 and 4. Ten independent replicated field trials were conducted: three in 2008, four in 2010, and three in 2011. Significant differences ( P ≤ 0.05) were observed for disease severity index of leaves, vascular root staining, and plant survival values among the elite germplasm lines in all 3 yr for the levels of resistance–response to FOV Races 1 and 4. Also, significant interactions among germplasm lines, FOV races (1 and 4), and evaluation sites indicated that germplasm lines differed in mechanisms of plant‐defense response for the two FOV races. Selected lines from programs in the states of Alabama, Arkansas, Louisiana, and Mississippi showed at least a moderate level of tolerance to both FOV races; however, several of these lines produced weak and coarse fibers. Based on these evaluations, many of the entries in public breeders' current elite upland germplasm pools may be more susceptible than expected to some FOV races, and sources of acceptable levels of resistance may be limited when tested under infestation levels that resulted in only 5 to 35% plant survival in susceptible check cultivars.